Perubahan Makna Kebangsaan Indonesia Setelah Menjadi Persatuan Indonesia Dalam Pancasila dan Dampaknya bagi Kehidupan Berbangsa Indonesia - John Titaley (Litbang STFT Widya Sasana Malang, 2022)
When Sukarno proposed the concept of Pancasila (Five Principles) in the meeting of the Investigative Body for the Preparation of Indonesian Independence (BPUPK) in 1945, Kebangsaan Indonesia (Indonesian Nationalism) was proposed by Sukarno as the first principle of Pancasila. However, Panitia Sembilan (the Committee of Nine), a sub-committee of BPUPK, changed the wording into Persatuan Indonesia (Unity of Indonesia). Persatuan Indonesia was accepted by BPUPK, but as the third principle. At the time, the region that would be known as Indonesia was ruled by three military governments, each controlled by a branch of the Japanese military. Panitia Sembilan feared that the occupying Japanese regime would give independence to several nations according to Japanese military rules rather than to Indonesia as one nation. An analysis on the impact of this change indicated a change in the fundamental philosophical and ethical meanings inherent in Kebangsaan Indonesia. While Kebangsaan Indonesia honored the diversity of Indonesia and valued the autonomy of each province in Indonesia, Persatuan Indonesia put the control at the central level, which eventually led to the conflict between the central and provincial governments.